A PROPOSED THEORETICAL FRAMEWORK OF DIGITAL FATIGUE AND DISCONTINUANCE IN LIVE STREAMING COMMERCE (LSC) - Azmi, Lina Fatini; Ahmad, Norasnita; Iahad, Noorminshah A. (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2026)
This study proposes a theoretical framework to explain how digital fatigue leads to discontinuance in live streaming commerce (LSC). Although gamified features such as personalization, rewards, timers, competition, and badges enhance consumer engagement, they may also trigger behavioral addiction and digital fatigue. Integrating Cognitive Load Theory, Flow Theory, Social Cognitive Theory, and Social Media Engagement Theory, the framework highlights how compulsive participation driven by gamified elements results in cognitive overload and emotional exhaustion, reducing satisfaction and increasing the likelihood of discontinuance. The proposed theoretical framework shows pathway of gamified antecedents → behavioral addiction → digital fatigue → discontinuance that demonstrates how overstimulation undermines sustained engagement. The study emphasizes the need for balanced gamification strategies that encourage mindful participation. Developing effective strategies to minimize digital fatigue can ultimately help businesses sustain user engagement and ensure the long-term viability of live streaming commerce. By extending discontinuance research into the LSC context, this study contributes a holistic model linking gamification, behavioral addiction, and digital fatigue, providing both academic insights and practical guidance for sustainable social commerce strategies.